The Belt and Road Initiative: Impacts on global maritime trade flows - Hercules E. Haralambides; Olaf Merk (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper analyses the potential impacts on global trade initiated by the Belt and Road Initiative. The Initiative is examined as a collection of planned transport-corridor developments and discusses their impact on maritime trade flows.
Keywords: 330; Verkehrsinfrastruktur; Entwicklungshilfe; Geopolitik; Internationale Wirtschaftsbeziehungen; China; Welt